Tinjauan Yuridis Penggunaan Mata Uang Asing sebagai Alat Pembayaran Dalam Transaksi di Wilayah Kedaulatan Negara Kesatuan Republik Indonesia (NKRI) - Winsherly Tan; Wahyudi Warianto (Fakultas Hukum, Universitas Internasional Batam, 2016)
In Indonesia various efforts were made to preserve the sovereignity of Rupiah as well as improving national and international trust in Rupiah. One of them is the implementation of regulation that obligates the use of Rupiah in all transactions that occur in Republic of Indonesia. However, there are some exception which allows the use of foreign currency in the country to a certain limit. This study is a normative method based on secondary data collected from literatures (library research) and analytic method of qualitative data. This study will discuss the use of foreign currency as a payment medium in the Republic of Indonesia and their consequences as stated in Undang – Undang Nomor 7 Tahun 2011 tentang Mata Uang and its validity as evidence in the court of justice. Based on this study, we observe results from 2 (two) problem formulations. First, the use of foreign currency as payment medium in transactions that occur in the Republic of Indonesia is allowed but only under certain condition and limited based on exception regulation to the use of Rupiah in the Territory of the Republic of Indonesia and the violations of the use of foreign currency by Undang – Undang Nomor 7 Tahun 2011 tentang Mata Uang have legal consequences on criminal sanctions. Second, invoices or documents of transactions using foreign currency when performed based regulations can be evidence, however, if invoices or documents based from illegal agreement or contract that breaking the law accordingly become void from the start.